U.S. college students’ perspectives on contraception and abortion post-Dobbs: the influence of socioeconomic privilege and gender inequity - Mann, Emily S.; McLennan, Jessica A.; Broussard, Kathleen (Frontiers in Public Health, 2024)
This study examined college students’ perspectives about contraception and abortion in the context of the United States Supreme Court's decision to eliminate the constitutional right to abortion in June 2022. Individual, semi-structured interviews were conducted between October 2022 and February 2023 with a convenience sample of 20 college students, ages 18-22, attending a public university in the southeastern United States. Qualitative data analysis revealed three main themes. First, most participants conveyed fear, dismay, and anger about the decision in Dobbs v. Jackson Women’s Health Organization to overturn Roe v. Wade and a few expressed concerns about potential restrictions on contraception. Second, women participants felt heightened pressure to continue or initiate use of a highly effective contraceptive method, with some lamenting inequitable experiences of the gendered contraceptive burden in their relationships with men. Third, when asked what they would do if they or their partner became pregnant while in college, most asserted they would seek abortion. Notably, participants assumed their socio-economic advantages would ensure their or their partner’s access to abortion, regardless of growing restrictions. The findings illustrate that among a group of relatively privileged young adults, the Dobbs decision simultaneously compelled their increased vigilance regarding contraceptive use and conferred the perception that they would not be personally impacted should they need an abortion.